Dispositional and performance-specific music performance anxiety in young amateur musicians - Spahn, Claudia; Tenbaum, Pia; Immerz, Anna; Hohagen, Jesper; Nusseck, Manfred (Frontiers in Psychology, 2023)
Research on Music Performance Anxiety (MPA) among amateur musicians is of great interest due to inconsistent results in literature. In addition, amateur music represents an important part of musical culture in Germany. Accordingly, the performance experiences of young wind players represent a relevant issue for research and musical practice. In the present study, 67 young amateur musicians of a brass choir were examined. Using two different questionnaires, both the dispositional MPA (K-MPAI) and the performance-specific MPA during a joint concert (Performance-specific Questionnaire for Musicians, PQM) were assessed. The PQM measures the symptoms of MPA, functional coping with MPA and self-efficacy before, during and after a specific performance. The PQM was completed by the musicians via an app directly after the concert. Results showed that about 90% of the young amateur musicians had a low dispositional MPA, but about 10% showed high values. For the concrete performance, however, musicians with high dispositional MPA also experienced a very moderate to low MPA in the concert. On average, the musicians were quite nervous before the performance. After the performance, they showed low levels of MPA. Three types of MPA found in previous studies could be confirmed among the amateur musicians, with three quarters being assigned to the positive type, showing low levels of symptoms associated with consistently high levels of self-efficacy and positive functional coping. The results provide a differentiated picture of different expressions of MPA in young amateur musicians. They also raise further questions about the correlation between dispositional and performance-specific assessment of MPA in musicians in general.